PENERAPAN PEWARNAAN GRAF UNTUK MENENTUKAN WISATA KULINER DI SAMARINDA - Wiwik Widiyatni; Vilianty Rafida; Hanifah Ekawati Sibali; Hannie Ardilla Kusuma (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2020)
Culinary tourism in an area is usually hunted by tourists. The problem that often arises is that many restaurants are available so that it makes tourists confused to choose a restaurant and takes a long time to decide on a choice of restaurants. Therefore, we need a system and method that can be applied to recommend restaurants. The restaurant recommendation application in this study was created to assist tourists in finding restaurants with the same menu choices. The method used is the Graph Coloring Method, the application development method used is Waterfall consisting of data analysis, technology analysis, system analysis, information analysis and user analysis. The results of this study are made an application to determine which restaurants can recommend restaurants with the same menu. Users can enter the menu as they wish then the application will recommend restaurants using a simple line coloring algorithm at the point. After processing the application will be able to display the results of restaurant recommendations with the same menu